Сейсмический вибратор с гидрообъемным генератором колебаний - Гаврилин А. Н. Алексей Николаевич; Говорин Р. А.; Иоппа А. В. Александр Валентинович; Крауиньш П. Я. Петр Янович; Смайлов С. А. Садык Арифович
опубл. 27.12.96